Correlation between forces acting on bolus and bolus behavior during swallowing using graph matrix obtained from computer simulations with the MPS method - Kamiya, Tetsu; Toyama, Yoshio; Hanyu, Keigo; Kikuchi, Takahiro; Michiwaki, Yukihiro (Food Science and Technology Research, 2024)
This study aims to analyze the forces acting on the organs from the bolus during swallowing, excluding direct organ contact forces. We simulated the swallowing process of healthy individuals ingesting thickened non-Newtonian foods using a swallowing simulator based on the moving-particle simulation method. The force vectors acting on the organs and the bolus shape were extracted at each time interval. A two-dimensional graph matrix was developed to visualize the temporal and spatial relationships between force and time for comprehensive interpretation and discussion. The graph matrix revealed that the bolus originated from tongue movement and was transferred between the oral cavity and pharynx, with coordinated movements of each organ occurring in pairs with balanced forces of the tongue and other organs. Information on the organ forces may offer a novel perspective for interpreting conventional mechanical indicators such as high-resolution manometry or tongue-pressure measurements.